First record of Felimare picta (Philippi, 1836) (Mollusca, Gastropoda, Chromodorididae) from Tobruk, Libyan coast - Said Rashad E.M.; Fitori Amani; Fituri Ali El; Mahdy Aldoushy (Oceanological and Hydrobiological Studies)
Biodiversity in the Mediterranean Sea has not yet been fully explored. There has been very little research on molluscs along the Libyan coast. An individual of the chromodoridid nudibranch Felimare picta (Philippi, 1836) was encountered during scuba diving at the Lido resort near the Tobruk bay basin. The sample was carefully transported to the lab in seawater, photographed, and identified. The current study revealed that Felimare picta was recorded for the first time on the Libyan coast. Despite Felimare picta being rather common in many Mediterranean regions, records of it on the southern Mediterranean coasts are extremely rare or absent. It may be concluded that this study represents not only the southernmost record of Felimare picta in the Mediterranean but also the first record of the species in Libya.